Application Of Nanoscale Polymer Colloid Carriers For Targeted Delivery Of The Brain-Derived Neurotrophic Factor Through The Blood-Brain Barrier In Experimental Parkinsonism - Kapitonova, Marina; Alyautdin, R. N.; Wan-Syazli, RWAL; Nor-Ashikin, M. N. K.; Ahmad, A.; Norita, S.; Dydykin, S.S. (Pirogov Russian National Research Medical University, 2018)
degeneration is considered to be pathognomic for the development of motor disfunction. Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family, which is considered to be a key regulator of neuronal plasticity. BDNF, being a large molecule, does not pass through the blood-brain barrier (BBB). Synthetic polymer nanoparticles (NP), covered by surfactant, provide the phenomenon of “Trojan hoarse” and enable BDNF to penetrate into the brain tissue. For modelling of parkinsonism we used an intraperitoneal (i.p.) injection of neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) which was injected to the C57BL/6 mice with subsequest treatment with normal saline (group 1), BDNF (group 2), nanoparticulate BDNF (group 3) and surfactant-coated nanoparticulate BDNF (group 4). After 90 min, 24 hours, 72 hours ad 7 days manifestations of parkinsonism were evaluated using behavioural tests of open field, rota-rod, assessment of the tremor, length of the body and pace. At the end of experiment the brain was sampled for histological evaluation of changes in the striatum and midbrain and concentration of BDNF in the brain tissues. The results of the experiments demonstrated that nanoparticulate BDNF covered with surfactant significanltly reduced rigidity of the skeletal muscles, oligokinesia and tremor, and also significantly increased BDNF concentration in the brain tissues.